2020
DOI: 10.1021/acs.jpca.0c02991
|View full text |Cite
|
Sign up to set email alerts
|

Nanoalloys of Metals Which Do Not Form Bulk Alloys: The Case of Ag–Co

Abstract: Ag and Co metals do not form macroscopic solid or liquid alloys. However, Ag m Co n clusters have been produced in dual-target dual-laser vaporization experiments, and the same occurs for other pairs of immiscible metals. We have performed density functional calculations to shed light on this phenomenon. The main result, obtained for clusters with sizes m + n not larger than 11, is that the cohesive energies justify that those clusters can be formed starting from free Ag and Co atoms, which is the case in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…The lowest energy structures obtained for free Con clusters are as follows: Co3 is a triangle, Co4 is a tetrahedron, Co5 is a square pyramid, Co6 is an octahedron, Co7 is a face-capped octahedron, and Co8 is a bi-capped octahedron. These results are in good agreement with previous studies [43][44][45]. As discussed by Ma et al [45], Co5 has two competing isomers with similar energy, the square pyramid and a trigonal bipyramid, and different studies predict one or the other as the lowest energy structure (a small distortion of the first structure leads to the second).…”
Section: Neutral and Charged C60con Complexessupporting
confidence: 92%
“…The lowest energy structures obtained for free Con clusters are as follows: Co3 is a triangle, Co4 is a tetrahedron, Co5 is a square pyramid, Co6 is an octahedron, Co7 is a face-capped octahedron, and Co8 is a bi-capped octahedron. These results are in good agreement with previous studies [43][44][45]. As discussed by Ma et al [45], Co5 has two competing isomers with similar energy, the square pyramid and a trigonal bipyramid, and different studies predict one or the other as the lowest energy structure (a small distortion of the first structure leads to the second).…”
Section: Neutral and Charged C60con Complexessupporting
confidence: 92%
“…Our results are consistent with a recent work 50 showing that core−shell clusters can be formed from pairs of metals (Co and Ag) that do not form macroscopic alloys. Similarly, we have found that the replacement of atomic gold by a Ni atom is highly endothermic at extended gold surfaces (1.59 eV), whereas it becomes exothermic for all triade atoms in 13-atom gold clusters (see Table 3).…”
Section: Resultssupporting
confidence: 93%
“…P. Marin et al [56] and A. Gomez Herranz et al [58] found out the reason for quenching of magnetic moments in these binary transition-metal clusters. The spatial spin density distribution of Zr n Ni clusters is also obtained (shown in figure 4).…”
Section: The Magnetic Moments and Partial Density Of Statesmentioning
confidence: 97%